ANALISIS KEBIJAKAN PENATAAN BUMD DI KABUPATEN BANGKA BARAT - Yuli Tirtariandi El Ansori; Eha Saleha (Jurnal Administrasi Publik, 2015)
The study was triggered by the problems in the west Bangka regency thathaving regional owned enterprises (BUMD) Bangka Barat Sejahtera.Since establishedbased on regulation no. 32.4 2011 it is considered failed searching for profit andcontribution to local government income. The case also occurring in many other areasin indonesia.Inefficiency and management problems,no focus in running businessesoften regarded as the major problems. Besides, BUMD has two functions as a publicservant and a profit maker for the local governments.This study adopted qualitativeapproaches.Data collection method is desk research, field observation, in-depthinterviews, and study of documents.Data analysis is carried out using an analysis of thetheory of the implementation of public policy and the concept of changeorganization.The last result obtained shows that the performance of BUMD) BangkaBarat Sejahtera doesnot reach maximum results. For example, in 2013 extrudedoverhead or rest loss about 300 million rupiah.